Gilberto Freyre in the press: the column "Persons, things and animals" in the magazine O Cruzeiro (1948-1967) - Schneider, Alberto Luiz (Revista de História, 2023)
This article aims to discuss the weekly column entitled “Persons, things and animals” of the Magazine O Cruzeiro, written by Gilberto Freyre and published between 1948 and 1967. Since Casa-Grande & Senzala (1933), Freyre achieved a prominent place in the Brazilian public life, with an extensive, but poorly studied participation in the press, whose scope may have had a decisive role in the propagation his interpretation of Brazil. The Magazine O Cruzeiro (Rio de Janeiro) was the main channel used by Freyre to reach large audiences, on a national scale, capable of routinizing a certain image of the nation, including the “racial democracy” idea.